‘Packham’s Triumph’ pears processed in different types of cutting and stored at different temperatures (Revista de Ciências Agroveterinárias, 2013)
The deterioration rate of minimally processed fruit is proportional to its respiratory rate, and the storage temperature is one of the factors that most influence it. Damages caused by cutting increase respiration and biochemical reactions such as browning. The objective of this study was to evaluate the effect of three types of cuts (sliced, diced and in halves) and two storage temperatures (5°C and 8°C) on the respiratory rate and color attributes of ‘Triumph Packhams’ pears stored in closed rigid polyethylene containers for seven days. After processing, the respiratory rate of pears slices stored at 8°C and pear cubes stored at 5 and 8°C was 62% higher than the pear cut into slices and stored at 5°C. On day seven, the respiratory rate was lower at 5°C and did not show any differences according to the type of cut. The type of cut affected the color parameter L (lightness). The fruit cut in alves and cubes did not show any browning (L = 75.4 to 75.9), as opposed to the sliced fruit (L = 72.8). The values of a*, C* and Hab indicated that slices stored at 8°C showed the highest browning rate.
Keywords: Respiration; Cold storage; Browning; Cut type; Minimally processed.